A virtual simulation study of the effects of laparotomy incision location and wound stiffness on abdominal wall mechanics - Lluís Tuset; Manuel López-Cano; Gerard Fortuny; Josep M. López; Joan Herrero; Dolors Puigjaner (Scientific Reports)
Abstract Incisional hernia (IH) is a common complication of laparotomy surgical procedures, influenced by factors such as incision location and surgical wound (SW) tissue strength, and the intra-abdominal pressure (IAP) levels the patient is subject to. In this study we use finite element simulations to investigate how these factors affect the abdominal wall (AW) deformation and the stress distribution on the tissues. Comprehensive geometric models of the AW were generated for five laparotomy incisions, namely midline, paramedian, pararectus, transverse supraumbilical, and subcostal oblique. Finite element simulations for IAP values between 4 and 20 kPa and with the SW tissue strength ranging from very soft to very stiff were conducted using the code Aster open-source software. Simulations revealed that as a general rule laparotomy incisions significantly impact AW mechanics when the SW tissue is soft. In particular, AW mechanics is more sensitive to SW strength in vertical incisions (midline, paramedian, pararectus). The resulting change of the SW dimensions with increasing IAP was also investigated. Softening the SW tissue led to substantial volume increases of the vertical incisions for a given IAP level. In addition, we analyzed stress levels in the SW tissue as well as in the surrounding muscles. A very soft SW may induce the appearance of regions with very high stress levels in the surrounding muscle tissue, heightening their rupture risk. This effect was especially noticeable for the midline incision. On the overall, we found that when the SW tissue is too tender transverse supraumbilical and subcostal incisions present the lowest risk of tissue ruptures whereas the midline incision is the most vulnerable one and the paramedian and pararectus incisions stand midway. In summary, the results of the present simulation provide full support for the clinical guidelines’ recommendation to avoid midline incisions in abdominal surgeries whenever possible.